2017
DOI: 10.1590/1807-7692bar2017160091
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Decision-Making: The Role of Self-Monitoring, Future Orientation, and Social Networks

Abstract: This study examines the influence of individual factors (self-monitoring, temporal orientation) on social networking, and their relationship with unethical decision-making. The study used surveys to measure the unethical intentions and social network data of 129 professionals. Data were analyzed using confirmatory factor analysis and structural equation modeling. The findings provided evidence that individual factors influence the development of social networks and, along with self-monitoring, the likelihood o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 73 publications
1
8
0
1
Order By: Relevance
“…Moreover, Santos et al (2013) found, that women were less related to corruption -in line with other researches (e.g. Bon et al, 2017), but at the same time have less propensity to report unethical acts. Impressive also are the findings of Behrens (2015) who suggested cultural aspects can even bring drawbacks (unethical use of) whistleblowing such as maligning other professionals.…”
Section: Unethical Silence In Order To Protect Social Capitalsupporting
confidence: 85%
See 4 more Smart Citations
“…Moreover, Santos et al (2013) found, that women were less related to corruption -in line with other researches (e.g. Bon et al, 2017), but at the same time have less propensity to report unethical acts. Impressive also are the findings of Behrens (2015) who suggested cultural aspects can even bring drawbacks (unethical use of) whistleblowing such as maligning other professionals.…”
Section: Unethical Silence In Order To Protect Social Capitalsupporting
confidence: 85%
“…Corporations should be concerned about densely closed networks which are relatively isolated from the rest of the whole group within the firm, and at the same time maintain individuals who function as brokers, connecting their network to others firms (Brass et al, 1998;Greve, Palmer, & Pozner, 2010). Tightly closed internal social networks could be broken and/or controlled by means of matrix organizations and more mobility between functions, avoiding groups connected as "honor among thieves" (Bon et al, 2017;Brass et al 1998). However, gender differences in networking are fundamental to be analyzed as some studies have concluded that men and women build different patterns of networks: women have much more closed networks than men (Ibarra, 1997;Burt, 1998), but at the same time some studies found evidence that women engage less in bribery (Tuliao & Chen, 2017).…”
Section: Corruption Preventionmentioning
confidence: 99%
See 3 more Smart Citations